2009
DOI: 10.1021/ac900019k
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Glucose Levels Using a Functionalized Hydrogel−Optical Fiber Biosensor: Toward Continuous Monitoring of Blood Glucose in Vivo

Abstract: Glucose-selective optical sensors were fabricated by incorporating 3-phenylboronic acid and a tertiary amine, dimethylaminopropylacrylamide, into a hydrogel matrix. Determination of glucose in solution is based on the glucose-induced contraction of the hydrogel. The gel was fabricated on the end of an optical fiber, and the optical length was measured by an interferometric technique. Previously it was found the gel could be tuned for enhanced glucose sensitivity and selectivity by varying the 3-phenylboronic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
110
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 31 publications
2
110
0
Order By: Relevance
“…Additionally, kinetics constants of 100 seconds and larger for swelling of phenylboronic acid incorporated hydrogels associated with changes in glucose have been reported [3]. These data indicated that the swelling kinetics associated with changes in ionic strength reflected the limit due to the diffusion of the network chains, while the others were limited by the rate of interactions among the involved species.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Additionally, kinetics constants of 100 seconds and larger for swelling of phenylboronic acid incorporated hydrogels associated with changes in glucose have been reported [3]. These data indicated that the swelling kinetics associated with changes in ionic strength reflected the limit due to the diffusion of the network chains, while the others were limited by the rate of interactions among the involved species.…”
Section: Discussionmentioning
confidence: 90%
“…The three solutions were mixed together yielding 10 wt% of AAM, 0.22, 0.44 and 0.88 mol% AMPSA relative to AAM, 3, 6 or 12 mol% Bis relative to AAM, and 0.15 mol% of initiator relative to AAM in the pregel solutions. Aliquots of the pre-gel solutions were deposited on the tip of the functionalized fiber and polymerized as described [1][2][3][4]45].…”
Section: Anionic Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…For these reasons, investigation on affinity binding sensors has been undertaken using various technologies, such as fluorescence (Ballerstadt et al, 2004(Ballerstadt et al, , 2006(Ballerstadt et al, , 2007Ballerstadt and Schultz, 2000) or viscosity-based (Beyer et al, 2001;Diem et al, 2004;Huang et al, 2009;Kuenzi et al, 2011;Zhao et al, 2007) principle. Recently, hydrogel-based sensors have emerged as promising tools for affinity sensing (Tierney et al, 2009a(Tierney et al, , 2009b. However, the development of biosensors for medical and biological applications that allows for long-term reversibility and stability remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, intensive investigations on affinity binding sensors have been carried out using different technics such as fluorescence (Ballerstadt, 2004) or viscosity measurements . Recently, hydrogelbased sensors have emerged as promising materials 295 for affinity sensing (Tierney, 2009). Despite many efforts towards the development of continuous biosensors for medical and biological applications, long term reversibility and stability remains a challenge.…”
Section: Introductionmentioning
confidence: 99%